Effects of Chitosan on Plasma Lipids and Lipoproteins: A 4-Month Prospective Pilot Study. (July 2014) - Rizzo, Manfredi; Giglio, Rosaria Vincenza; Nikolic, Dragana; Patti, Angelo Maria; Campanella, Claudia; Cocchi, Massimo; Katsiki, Niki; Montalto, Giuseppe
Chitosan can favorably modulate plasma lipids, but the available data are not conclusive. We evaluated the effect of chitosan on plasma lipids and lipoproteins in 28 patients with plasma triglyceride levels >150 mg/dL (mean age: 63 ± 12 years), not taking other lipid-lowering agents. All patients received a chitosan derived from fungal mycelium (Xantonet, Bromatech, Italy) at a fixed dose of 125 mg/d in addition to their current medications for 4 months. Polyacrylamide gel electrophoresis was used to measure low-density lipoprotein (LDL) subclasses. After treatment, total cholesterol reduced by 8%, LDL cholesterol by 2%, and triglycerides by 19%, with a concomitant 14% increase in high-density lipoprotein cholesterol. We also found a beneficial effect of chitosan on LDL subclasses, with a significant increase in LDL-2 particles (from 37 ± 8% to 47 ± 8%, P = .0001) and a decrease (although not significant) in atherogenic small, dense LDL. Whether these findings may affect cardiovascular risk remains to be established in future studies.